CLINICAL FEATURES AND CORRECTION OF DENTITION ABNORMALITIES AND MALFORMATIONS IN PEDIATRIC PATIENTS (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Between 2023 and 2025, clinical assessments and treatment were carried out for 120 children aged 10 to 18 years presenting with occlusal deformities of the dental arches, alongside a control group of 35 healthy peers. Various types of malocclusions were observed, including midline asymmetry in 12 patients (10%), infraocclusion in 24 cases (20%), supraocclusion in 18 cases (15%), and partial tooth loss in 20 children (16.67%). The overall dental caries prevalence in this age group was recorded at 68.7%. An increase in vertical facial dimension was noted, particularly among adolescents aged 14–18, possibly influenced by physiological factors. The treatment protocol developed and recommended in this study showed superior effectiveness compared to conventional approaches, achieving a success rate of 93.4%.